2016
DOI: 10.1590/0102-311x00121114
|View full text |Cite
|
Sign up to set email alerts
|

Litigio judicial y el derecho a la salud en Argentina

Abstract: Resumen El propósito de este trabajo es explorar el perfil del litigio por el acceso a la atención de la salud, tramitado ante la Corte Suprema de Justicia Argentina, y reflexionar sobre su potencial para influir sobre la equidad y el derecho a la salud, en el marco de un proceso de crecimiento de la judicialización. Se llevó a cabo un análisis documental de 125 litigios con sentencias dictadas entre 1994 y 2013. Se observó una preeminencia de la reclamación individual (88% reclamantes personas físicas individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
3
0
5
Order By: Relevance
“…In Brazil, lawsuits are also favourable in a percentage of 90.0% . By contrast, in Argentina, 75.0% of decisions were favourable, according to Gotlieb et al In Costa Rica, another study found 60.0% of favourable judgments…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, lawsuits are also favourable in a percentage of 90.0% . By contrast, in Argentina, 75.0% of decisions were favourable, according to Gotlieb et al In Costa Rica, another study found 60.0% of favourable judgments…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, the final regulation mandates the health ministry build a list of rare diseases and their respective high-cost treatments, but stops short of describing reimbursement parameters. In Colombia and Argentina, litigation for access has been described as routine [40,41]. All three governments are focused on price control, centralized purchasing, and new medicine evaluation agencies to limit budget shock and to prioritize value.…”
Section: Perumentioning
confidence: 99%
“…La judicialización se ha limitado a operar como un mecanismo de protección de los derechos individuales, pero sin verdadera incidencia en las políticas públicas de salud. Y así, mientras el litigio por acceso a la atención de la salud mantenga su actual patrón individualista, difícilmente podrá desarrollar todo su potencial para garantizar el efectivo respeto por el derecho a la salud 32 .…”
Section: La Objeción De La Litigación Como Elemento Principal De Junclassified